Long-Term Metabolic Effects of High Birth Weight: A Critical Review of the Literature - Palatianou, M. E.; Simos, Y. V.; Andronikou, S. K.; Kiortsis, D. N. (Hormone and Metabolic Research, 2014)
Recent studies in USA, Europe, and across the world have revealed a continuous increase of mean birth weight in the last 2 decades. Strong evidence exists from several studies indicating that individuals born with a low birth weight are more likely to present cardiometabolic complications in later life. So far, the long-term consequences of high birth weight have not been clearly defined. This review examines the role of high birth weight on the development of cardiometabolic consequences (obesity, body composition, type 2 diabetes mellitus, and cardiovascular disease) in childhood and adulthood. The majority of the studies show that high BW is associated with an increased risk for obesity. To a certain extent high birth weight affects diseases of the heart and circulatory, but does not constitutes a risk for the development of type 2 diabetes mellitus in the general population. Maternal glycemia and the subsequent fetus hyperinsulinemia appear to be the key component for increased fetal growth. With the increase in incidence of diabetes mellitus and obesity over the years, the number of high birth weight infants is likely to increase. The elucidation of the relationship between high birth weight and the cardiometabolic disorders will be particularly important.
Keywords: birth weight; obesity; diabetes; cardiovascular disease